2023
DOI: 10.3389/fneur.2023.1103270
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent association analysis between serum uric acid and spontaneous hemorrhagic transformation in patients with ischemic stroke

Abstract: ObjectiveThe association between serum uric acid (UA) and spontaneous hemorrhagic transformation (HT) has been seldom studied, and the role of UA in spontaneous HT remains unclear. This study aims to investigate the sex-dependent association between UA and spontaneous HT in patients with ischemic stroke.MethodWe retrospectively included patients with ischemic stroke in a tertiary academic hospital between December 2016 and May 2020. Patients were included if they presented within 24 h after the onset of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There are gender differences in UA degrees, and studies have confirmed that the average UA degree is significantly lower in female than in male due to estrogen 3, 46 . A sex-stratified analysis of one study we brought to a close demonstrated that 3 , UA degrees in male were significantly higher than those in female, and the incidence of HT was lower than that in female, which corresponded with earlier discoveries, as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…There are gender differences in UA degrees, and studies have confirmed that the average UA degree is significantly lower in female than in male due to estrogen 3, 46 . A sex-stratified analysis of one study we brought to a close demonstrated that 3 , UA degrees in male were significantly higher than those in female, and the incidence of HT was lower than that in female, which corresponded with earlier discoveries, as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggested that a lower SUA/SCr ratio indicated a likelihood of poor functional outcome in AIS patients who underwent MT. Although prior research has suggested a link between higher SUA levels and spontaneous haemorrhagic transformation [40] and some studies reported the link between SUA and haemorrhagic transformation or sICH in AIS patients after reperfusion therapy [41,42], there has been no research investigating the relationship between SUA/SCr ratio and symptomatic haemorrhage. Our study observed no association between SUA/SCr ratio and sICH in patients undergoing MT.…”
Section: Discussionmentioning
confidence: 99%